Using EViews for undergraduate econometrics - Hill, R. Carter; Griffiths, William E.; Judge, George G. (New York : Wiley, 2001)
The book is a supplement to Undergraduate Econometrics, it shows how to perform the computations, step by step, in each chapter of that book using EViews.
CD-ROM in pocket attached to inside front cover.
Previous ed.: 1997.
uaj 30/04/13
Loans
Keywords: Econometrics; Eviews